Incidence of applying the task-based learning method and group work technique to develop english speaking production on students attending the 7th year of basic education at Sagrados Corazones School during the scholar year 2011-2012 - Rivera Arcos, Marco Orlando (2012)
In recent years, various explanations and possible solutions have been given for the low quality of English speaking achievement of the Ecuadorian students from most educational institutions. Consequently, this research has been focused on applying the use of Task-based Approach in learning process, in order to improve the speaking production for students attending the 7th year of Basic Education at Sagrados Corazones School. Once the problem and sub problems were detected, dependent and independent variables were determined in order to elaborate the general and the specific objectives. The theoretical frame has been categorized to obtain the main items, which allowed getting the required information to set up a proposal. The purpose of this study is to develop English speaking ability at the Sagrados Corazones School through task-based learning. The methodology will be developed by the quasi experimental design, that is formed by a control group and an experimental group using pretests and posttests that gave us two groups in order to measure the results of this study through the appropriate statistical process ( t-test). The informants are 40 learners gained via random sampling. The instruments used for collecting data were unit lesson plans, a pre-post speaking test, a teacher¿s observation form, learners¿ self-assessment form, and group work assessment. The data were statistically analyzed by mean, standard deviation, and t-test for dependent samples. The results indicated that the English speaking ability of school students through task-based learning after the experiment will be significantly higher. The conclusions and recommendations of the research are based on the findings of the investigation, and then it was necessary to elaborate the proposal part in order to socialize the results organizing seminars for teachers.